The carbon budget in the northern Adriatic Sea, a winter case study. Issue 7 (24th July 2014) - Catalano, G.; Azzaro, M.; Bastianini, M.; Bellucci, L. G.; Bernardi Aubry, F.; Bianchi, F.; Burca, M.; Cantoni, C.; Caruso, G.; Casotti, R.; Cozzi, S.; Del Negro, P.; et al.
Abstract This paper presents a winter carbon budget for the northern Adriatic Sea, obtained through direct measurements during two multidisciplinary cruises and literature data. A box model approach was adopted to integrate estimates of stocks and fluxes of carbon species over the total area. The oligotrophy at the basin scale and the start of primary productivity well before the onset of spring stratification were observed. In winter, the system underwent a complete reset, as the mixing of water masses erased any signal of previous hypoxia or anoxia episodes. The northern Adriatic Sea was phosphorus depleted with respect to C and N availability. This fact confirms the importance of mixing with deep‐sea water for P supply to biological processes on the whole. Despite the abundant prokaryotic biomass, the microbial food web was less efficient in organic C production than phytoplankton. In the upper layer, the carbon produced by primary production exceeded the fraction respired by planktonic community smaller than 200 µm. On the contrary, respiration processes prevailed in the water column below the pycnocline. The carbon budget also proved that the northern Adriatic Sea can be an effective sink for atmospheric CO2 throughout the entire winter season.